Estudo da tensão residual através de difração de raios X em aço inoxidável duplex submetido a diferentes tratamentos térmicos - Santos, Camila Zangerolame (2012)
The evolution of residual stresses in a duplex stainless steel with different thermal treatments was investigated by X-ray diffraction. In this work, samples of steel UNS S32304 were analyzed. These materials have a two-phase microstructure of ferrite and austenite in approximately equal volume fractions. The samples were characterized in detail by X-ray diffraction and AC magnetic susceptibility. To determine the residuals stresses in the phases, the method of sin2ψ was used. This method is based on the measurement of peak positions for a given hkl reflection and for various directions of the scattering vector. It was observed that due to heat treatment, there is a residual compressive stresses for both the ferritic phase and for the austenitic phase.